The Modern Mechanism of the Effect of Vitamins on the Health of Women during Menopause - Nusratoy, Ochilova (Journal of Science in Medicine and Life, 2024)
Menopause usually occurs in women aged 47-55 years. This implies the cessation of the functioning of the ovaries and at the same time changes in the hormonal level, the loss of menstruation and the ability to conceive. During menopause, a comprehensive approach is required, including taking medications, vitamins, dietary supplements, and homeopathy. They are designed to alleviate the woman's condition, normalize the hormonal level and reduce the risk of possible complications.